IMPACT OF LONG-TERM CLIMATE CHANGE AND SEA-LEVEL FLUCTUATION ON MISSISSIPPIAN TO PERMIAN MID-OCEANIC ATOLL SEDIMENTATION (AKIYOSHI LIMESTONE GROUP, JAPAN) - Sano H. (My University, 2006)
To understand the impacts of long-term climatic episodes and sea-level changes on mid-oceanic atoll sedimentation, the stratigraphic changes of litho- and bio-facies, and stratigraphic levels of freshwater diagenetic alteration and biostratigraphic discontinuity of the Akiyoshi Limestone Group (upper Viséan to upper Capitanian) were reviewed. This group records approximately 70 million years of atoll sedimentation in a mid-oceanic realm of the Panthalassa Ocean, which developed nearly synchronously with the Late Paleozoic Gondwana glaciation. The entire succession of the Akiyoshi Limestone Group was divided into four facies associations; skeletal-oolitic grainstone, muddy limestone, muddy limestone-skeletal grainstone, and reefal limestone associations. Skeletal-oolitic grainstone and reefal limestone associations (upper Viséan to Bashkirian) are characterized by an abundance of oolite and crinoidal grainstone, and reef facies of warm-adapted metazoan reef-builders (corals, Chaetetes, and bryozoans), respectively. Characteristics of skeletal-oolitic grainstone and reefal limestone associations indicate their deposition in a warm climate with elevated sea-level. Muddy limestone association (Moscovian to Kasimovian) records the demise of the warm-adapted metazoan reef builders and frequent emergence events of the buildup. Many geochemical data support the significant drop in temperature during Moscovian through Kasimovian time. These depositional and biotic events of muddy limestone association indicate that its sedimentation was strongly affected by cool climate and generally low sea-level. Muddy limestone-skeletal grainstone association is characterized by an upward-increasing significance of calcimicrobes, calcareous algae, and calcisponges. The succession records less frequent emergence events than that of muddy limestone association II. These characters reflect a warming climate and sea-level rise in Gzhelian to Capitanian time. The climate episodes and sea-level changes interpreted from the Akiyoshi Limestone Group generally correspond to the global trend of Mississippian to Permian long-term climatic change and sea-level fluctuation related to the major glacial events of Gondwana glaciation. The late Viséan to Bashkirian warm climate and elevated sea-levels, Moscovian to Kasimovian cooling and sea-level lowering, and Gzhelian to Capitanian warming and sea-level rise recorded in the Akiyoshi buildup are comparable to the global climate model and sea-level fluctuation, which contain Early to Middle Mississippian pre-glacial warm climate and highstands, Middle to Late Pennsylvanian cooling and related glacio-eustatic sea-level fluctuation at the culmination of Gondwana glaciation, and Early to Middle Permian global warming and sea-level rise due to the retreat of Gondwana ice sheets. Akiyoshi atoll sedimentation was most significantly affected Pennsylvanian global cooling and related sea-level lowering, but their impact was short-lived. The onset of the cooling and frequent emergence events in the Akiyoshi buildup occurred delayed, approximately 10 millions years later than that of comparable episodes on the Pangean shelves. The post-glacial warming in the Akiyoshi buildup started at least several millions of years earlier than in epicontinental seas of the Pangea. This phenomenon may be due to the palaeoposition of the Akiyoshi buildup in a mid-oceanic realm of the Panthalassa Ocean. © 2005 Elsevier B.V. All rights reserved.
Keywords: AKIYOSHI LIMESTONE GROUP; ATOLL CARBONATES; EMERGENCE; LATE PALEOZOIC GLOBAL COOLING; PANTHALASSA OCEAN; Permian; Gzhelian; Kasimovian; Moscovian; Bashkirian; Mississippian; Pennsylvanian; Paleozoic::Permian; Палеозой::Пермская; Paleozoic::Carboniferous::Pennsylvanian::Upper::Gzhelian; Палеозой::Каменноугольная::Верхний::Гжельский; Paleozoic::Carboniferous::Pennsylvanian::Upper::Kasimovian; Палеозой::Каменноугольная::Верхний::Касимовский; Paleozoic::Carboniferous::Pennsylvanian::Middle::Moscovian; Палеозой::Каменноугольная::Средний::Московский; Paleozoic::Carboniferous::Pennsylvanian::Lower::Bashkirian; Палеозой::Каменноугольная::Нижний::Башкирский; Paleozoic::Carboniferous::Mississippian; Paleozoic::Carboniferous::Pennsylvanian